The advantage of matcha green tea over other drinks: A comprehensive review - Starzomska, Dominika; Gajdzińska, Natalia; Basiura, Karolina; Salwa, Adam; Rymaszewska, Katarzyna; Puchała, Justyna (Quality in Sport, 2024)
Matcha green tea is a finely ground powder made from specially cultivated and processed leaves of Camellia sinensis. Key components of matcha include catechins, caffeine, theanine, fat-soluble vitamins, insoluble dietary fibers, chlorophylls, and proteins. Studies indicate that matcha green tea may offer various health benefits, such as reducing the effects of aging, alleviating stress, and mitigating cognitive impairment. Furthermore, regular consumption of matcha tea supports gut microbiome health, enhances immune function, and reduces the risk of inflammation as well as certain types of cancer. This review strengthens the connection between regular intake of matcha green tea and overall well-being.